Regional Variations in Outpatient Antibiotic Prescribing in Germany: A Small Area Analysis Based on Claims Data - Oliver Scholle; Marieke Asendorf; Christoph Buck; Susann Grill; Christopher Jones; Bianca Kollhorst; Oliver Riedel; Benjamin Schüz; Ulrike Haug (MDPI AG, 2022)
A comprehensive small area description of regional variations in outpatient antibiotic prescribing in Germany is lacking. Using the German Pharmacoepidemiological Research Database (GePaRD), a claims database covering ~20% of the German population, we determined the age- and sex-standardized prescription rates of antibiotics (number of outpatient prescriptions per 1000 persons/year). We calculated these prescription rates overall and on the level of 401 German districts for the calendar years 2010 and 2018. In 2018, the standardized prescription rate of antibiotics in the total study population was 23% lower than in 2010 (442 vs. 575 per 1000 persons/year). Among 0-17-year-olds, prescription rates across districts ranged from 312 to 1205 in 2010 and from 188 to 710 in 2018 per 1000 persons/year; among adults (≥18 years), they ranged from 388 to 841 in 2010 and from 300 to 693 in 2018 per 1000 persons/year. Despite the overall decline in outpatient antibiotic prescribing between 2010 and 2018, regional variations at the district level remained high in all age groups in Germany. Identifying reasons that explain the persistently high prescription rates in certain regions will be helpful in designing effective and tailored measures to further improve antibiotic stewardship in these regions.